Pemberdayaan Penyandang Disabilitas Melalui Balai Latihan Kerja Bhakti Luhur - Lorentius Goa (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2020)
People with disabilities are a hot topic to be discussed in various developed countries including our country, Indonesia. The reason is, people with disabilities are a group of minorities who are often neglected in fulfilling their rights. One of the ways for people with disabilities can have a decent life is through empowerment. The Bhakti Luhur Foundation itself has the vision to empower people with disabilities through various activities, one of which is through a job training center accompanied by professional staff. People with disabilities who are empowered in this job training center are people with disabilities who can train. The empowerment carried out is the manufacture of household furniture, household utensils, manual paving stone production, woodcraft for playgroups, painting and knitting painting (streaming), printing and offsetting, making plant pots, ornamental plants, and raising tilapia and catfish.